2007
DOI: 10.1128/aem.02880-06
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Lignocellulose-Derived Inhibitors on Growth of and Ethanol Production by Growth-Arrested Corynebacterium glutamicum R

Abstract: In cellulosic ethanol production, pretreatment of a biomass to facilitate enzymatic hydrolysis inevitably yields fermentation inhibitors such as organic acids, furans, and phenols. With representative inhibitors included in the medium at various concentrations, individually or in various combinations, ethanol production by Corynebacterium glutamicum R under growth-arrested conditions was investigated. In the presence of various inhibitors, the 62 to 100% ethanol productivity retained by the C. glutamicum R-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(52 citation statements)
references
References 30 publications
2
47
0
Order By: Relevance
“…The cell concentration was 60 g CDW/L. Data show averages and standard deviations from four independent experiments engineered strains showing superior production performance compared to the previously reported ethanol-producing C. glutamicum ΔldhA-pCRA723 strain that exhibited maximum ethanol titer of 78 g/L and an ethanol yield of 53 % (Inui et al 2004a;Sakai et al 2007). This study also demonstrated that metabolic engineering of C. glutamicum for ethanol production from a sugar mixture and engineered strain CRZ18-pCRB219 exhibited production of high concentration of ethanol (83 g/L) from the sugar mixture.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The cell concentration was 60 g CDW/L. Data show averages and standard deviations from four independent experiments engineered strains showing superior production performance compared to the previously reported ethanol-producing C. glutamicum ΔldhA-pCRA723 strain that exhibited maximum ethanol titer of 78 g/L and an ethanol yield of 53 % (Inui et al 2004a;Sakai et al 2007). This study also demonstrated that metabolic engineering of C. glutamicum for ethanol production from a sugar mixture and engineered strain CRZ18-pCRB219 exhibited production of high concentration of ethanol (83 g/L) from the sugar mixture.…”
Section: Discussionmentioning
confidence: 96%
“…Nonetheless, this study clearly demonstrates that overexpression of glycolytic genes is a useful way to improve productivity of bioprocesses using oxygen-deprived C. glutamicum. Additionally, the constructed strain, CRZ18-pCRB219, has the potential to be used for the production of ethanol from lignocellulosic biomass under conditions of oxygen deprivation, where it shows high tolerance to inhibitory compounds generally found in lignocellulose hydrolysates (Sakai et al 2007). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was isolated in an effort to screen for L-glutamate-producing bacteria (Kinoshita et al 2004;Udaka 1960). Since its discovery, C. glutamicum has been widely investigated and applied in industrial production of various amino acids and vitamins (Hermann 2003;Leuchtenberger et al 2005;Becker et al 2009), and recently of bio-based chemicals such as succinate (Okino et al 2008a), lactate (Okino et al 2008b), ethanol (Inui, et al 2004;Sakai et al 2007), 1,4-diaminobutane (Schneider and Wendisch 2010), 1,5-diaminopentane (Mimitsuka et al 2007), pyruvate (Wieschalka et al 2012), and isobutanol (Blombach et al 2011). Due to its industrial importance, the genomes of several strains of C. glutamicum have been sequenced (Kalinowski et al 2003;Ikeda and Nakagawa 2003;Yukawa et al 2007;Lv et al 2011Lv et al , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, arabinose utilization was also achieved, whereby the genes araA, araB, and araD were also derived from E. coli [163]. An interesting study recently investigated the tolerance of C. glutamicum to toxic compounds such as furfurals or phenols, typically present in lignocellulosic raw materials [164]. These compounds cause significant inhibition of growth.…”
Section: Utilization Of Alternative Substratesmentioning
confidence: 99%